Prevalence of hepatitis B surface antigen (HBsAg) in asymptomatic pregnant women and in the cord blood of their newborns - Jha, Dharmendra Kr.; Jha, Anshu Kr. (International Journal Of Community Medicine And Public Health, 2018)
Background: In a developing country like India there is very high incidence and prevalence of hepatitis B. The disease is easy to prevent than to treat. Pregnant females are exposed more to risk factors than the general population which makes them a more apt candidate for HBsAg screening. This shall help both the mother (in terms of treatment) and newborn (in terms of prophylaxis and if not successful then, treatment). Methods: This study was conducted on 111 patients who were divided into two groups of asymptomatic cases and symptomatic cases i.e. those patients who were jaundiced. ELISA was used for detection of HBsAg in the maternal and the cord blood of their newborn. Results: Maximun incidence of sero-positivity was seen in age group between 20-25yrs and second pregnancy was associated with maximum HBsAg positivity. Asymptomatic cases showed only 10.41% sero-positivity whereas it was 60% in clinically jaundiced cases (p<0.05). Also rate of vertical transmission was 66.6% in the diseased group. Obstetric complications like premature labour, early rupture of membrane were also observed in the study. Conclusions: This study helped us to know the prevalence and the various other association of HBsAg positivity both in clinically asymptomatic cases and symptomatic cases. Thus we conclude that HBsAg screening should be mandatory for all pregnant females and in areas where resources a scarce at least high risk cases should be screened. This shall help to break the chain of mother to child transmission (MTCT) of this dreaded disease.